Pengaruh Manajemen Pembelajaran terhadap Hasil Belajar Siswa SD Al Ma’soem di Masa Pandemi - Husni Mubarok; Uswatun Khasanah; Aliyya Ishlah Farah; Khoirun Nisa; Novi Musanadah; Roikhatun Haniyyah (Arus Jurnal Pendidikan, 2021)
This writing aims to study the Effect of Management on Student Learning Outcomes at Al-Ma'soem Elementary School during the Pandemic. This writing uses descriptive qualitative research methods in obtaining data. So as to be able to explain the influence of learning management on student learning outcomes during the pandemic. In this study, the aspect studied was learning management at Al-Ma'soem Elementary School such as methods and strategies in teaching during the pandemic in order to achieve a goal, with good management, of course, it would affect student learning outcomes. Thus, with this writing, it is hoped that good learning management can affect student learning outcomes so that a learning goal can be achieved.